2013
DOI: 10.1177/1753193413491041
|View full text |Cite
|
Sign up to set email alerts
|

Scaphoid nonunions in skeletally immature adolescents

Abstract: Scaphoid nonunions in children requiring operative treatment are rare. The aim of this study was to analyze our own patient population of the last 13 years to assess the postoperative outcome of these operations. Seven patients, under aged 14 years, were treated for scaphoid nonunions. Patients were clinically and radiologically examined and subjective outcomes were measured, such as the visual analogue pain scale (VAPS), Disability of the Arm, Shoulder and Hand (DASH) score, and Krimmer score. All patients sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…First, although there is no set age limit, the Quick DASH questionnaire was developed for adults. However, 87.8% of our patients were older than 8 years of age and thus able to fully understand the questions and answer independently [18][19][20][21]. In addition, the DASH questionnaire has already been used to measure disability and symptom severity in a variety of arm disorders in children [14][15][16]20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, although there is no set age limit, the Quick DASH questionnaire was developed for adults. However, 87.8% of our patients were older than 8 years of age and thus able to fully understand the questions and answer independently [18][19][20][21]. In addition, the DASH questionnaire has already been used to measure disability and symptom severity in a variety of arm disorders in children [14][15][16]20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The Quick DASH questionnaire has the advantage of enabling a reproducible comparison of postsurgery functional outcome over time in patients with this type of fracture, including the capacity to detect and differentiate small and large changes in disability [18,19]. It has been shown that the Quick DASH questionnaire can be used to measure disability and symptom severity in a variety of arm disorders in children [14][15][16]20,21]. Canavese and colleagues used it to evaluate the functional outcome of proximal humerus fractures, Colovic and colleagues used it to assess elbow function after supracondylar fractures, Bae and colleagues used it in children with established malunion of the clavicle, and Behr and colleagues used it to evaluate scaphoid nonunion in skeletally immature adolescents [14][15][16]20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Fernandez et al 5 treated six cases of non-union of forearm shaft fractures in children after intramedullary nailing. Behr et al 6 reported seven cases of scaphoid, Cortes et al 7 treated one case of non-union following subtrochanteric femoral fracture in a child. Pourtaheri8 reported one case of clavicle non-union.…”
Section: Discussionmentioning
confidence: 99%
“…Though most pediatric scaphoid fractures have a good prognosis with conservative management (Weber, Fricker, & Ramseier, ), scaphoid nonunion has been reported (Ahmed, Ashton, Tay, & Porter, ; Behr et al, ; Elhassan & Shin, ; Reigstad, Thorkildsen, Grimsgaard, Reigstad, & Rokkum, ). Since this lesion is a rarity, however—with a nonunion rate of just 0.8% (Elhassan & Shin, )—management experience is limited and optimal treatment remains controversial (Elhassan & Shin, ).…”
Section: Introductionmentioning
confidence: 99%